Documenting Events:: Thai Archival Foundations and their Evolution in Contemporary Society - Sucha-xaya, Naya (Journal of Letters, 2021)
Before Thai archival management was influenced by Western concepts, the Thai word for archives, jotmaihet, referred to the documentation of events. This definition differs from that of modern archives, which emphasizes the keeping of records with ongoing value. This article studies the roots of Thai archival practice, investigating the evolution of documentation in Thai society as well as its underlying principles. The research employs content analysis of various Thai archives and interviews with Thai national archivists and experts in documentation. The findings confirm that documentation is foundational to Thai archival practice, typically having been performed by scribes or archivists who themselves witnessed the events they documented. This practice may have been influenced by the Chinese tradition, and has been adapted until the present day in the National Archives of Thailand. At the same time, documentation of events has also been practiced by various civic groups to pass on knowledge and memories. Documentation has increasingly regained an important role in contemporary society, in which people have the power to document and manage archives themselves. Thus, it is recommended that a participatory approach should be pursued to widen and diversify documentation practices through technological connectivity.